2006
DOI: 10.1534/genetics.105.051003
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of Selection With Equalization of Parental Contributions in Conservation Programs: An Experimental Test With Drosophila melanogaster

Abstract: Equalization of parental contributions is one of the most simple and widely recognized methods to maintain genetic diversity in conservation programs, as it halves the rate of increase in inbreeding and genetic drift. It has, however, the negative side effect of implying a reduced intensity of natural selection so that deleterious genes are less efficiently removed from the population with possible negative consequences on the reproductive capacity of the individuals. Theoretical results suggest that the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…Experiments, particularly, involving Drosophila (Loebel et al, 1992;Borlase et al, 1993, Montgomery et al, 1997 have demonstrated the advantages of equalising the contributions of individuals, rather than producing a random number of offsprings. A recent study by Rodríguez-Ramilo et al (2006) assessed the effect of conservation strategies on the accumulation of deleterious mutations.…”
Section: Practical Applications Of Pedigree-based Managementmentioning
confidence: 99%
“…Experiments, particularly, involving Drosophila (Loebel et al, 1992;Borlase et al, 1993, Montgomery et al, 1997 have demonstrated the advantages of equalising the contributions of individuals, rather than producing a random number of offsprings. A recent study by Rodríguez-Ramilo et al (2006) assessed the effect of conservation strategies on the accumulation of deleterious mutations.…”
Section: Practical Applications Of Pedigree-based Managementmentioning
confidence: 99%
“…To assess the efficiency of EC in different instances, the fitness performance under EC must be compared to that obtained with no management (NM), when family contributions randomly depend on family 1 fertility and offspring viability. This has been achieved for some specific cases using computer simulation and transition matrix predictions (Schoen et al 1998;Fernández and Caballero 2001;Theodorou and Couvet 2003) or carrying out Drosophila experiments (Borlase et al 1993;Rodríguez-Ramilo et al 2006) but, so far, no general approach has been advanced to obtain analytical predictions for the relative advantage of EC and NM methods. I have adapted the above ''shift approximation'' to the case where EC is applied, considering selection operating either on fecundity or on viability, and I use these approximations to infer the conditions for which the EC method of maintenance is superior under various sets of mutational parameters.…”
mentioning
confidence: 99%
“…Thus, the Borlase et al results are consistent with our predictions under a variety of mutational parameters, both for fertility and for viability. Rodríguez-Ramilo et al (2006) maintained Drosophila populations with N 9 ¼ 100 or 20 for 35 generations using NM or EC. In large populations, relative viability declined to $0.8, with no detectable difference between methods, while with N9 ¼ 20, relative viability declined to $0.6, showing a small but consistent advantage for EC (see their Figure 5B).…”
mentioning
confidence: 99%
“…On the other hand, for moderately larger populations (N = 20 or N = 100, Rodriguez-Ramilo et al 2006), EC was found to have small fitness consequences both in the short and the long term. Numerical and simulation approaches have also shown that, in agreement with theoretical predictions, EC induces a strong fitness decline in the medium term if the rate of fecundity decline caused by deleterious mutation is important (Schoen et al 1998;Fernández and Caballero 2001), while the long term consequences for viability are minor (Fernández and Caballero 2001;Theodorou and Couvet 2003).…”
mentioning
confidence: 84%